Effect of Histophilus somni on Heart and Brain Microvascular Endothelial Cells. (July 2017) - O'Toole, D.; Hunter, R.; Allen, T.; Zekarias, B.; Lehmann, J.; Kim, K. S.; Grab, D.; Corbeil, L. B.
Histophilus somni is a pathogenic gram-negative bacterium responsible for pneumonia and septicemia in cattle. Sequelae include infectious thrombotic meningoencephalitis (ITME), myocarditis, arthritis, and abortion. These syndromes are associated with widespread vasculitis and thrombosis, implicating a role for endothelium in pathogenesis. Histopathologic and immunohistochemical investigation of 10 natural cases of bovine H. somni myocarditis and 1 case of ITME revealed intravascular H. somni in large biofilm-like aggregates adherent to the luminal surface of microvascular endothelium. Ultrastructurally, bacterial communities were extracellular and closely associated with degenerating or contracted endothelial cells. Histophilus somni was identified by bacterial culture and/or immunohistochemistry. Western blots of the bacterial isolates revealed that they expressed the immunodominant protective 40 kDa OMP and immunoglobulin-binding protein A (IbpA) antigens. The latter is a large surface antigen and shed fibrillar antigen with multiple domains. The cytotoxic DR2Fic domain of IbpA was conserved as demonstrated by polymerase chain reaction. Treatment of endothelial cells in vitro with IbpA in crude culture supernatants or purified recombinant GST-IbpA DR2Fic (rDR2) cytotoxin induced retraction of cultured bovine brain microvascular endothelial cells. By contrast, no retraction of bovine endothelium was induced by mutant rDR2H/A with an inactive Fic motif or by a GST control, indicating that the cytotoxic DR2Fic motif plays an important role in endothelial cell retraction in vasculitis. The formation of biofilm-like aggregates by H. somni on bovine microvascular endothelium may be fundamental to its pathogenesis in heart and brain.